Single-cell transcriptomics identifies a WNT7A-FZD5 signaling axis that maintains fallopian tube stem cells in patient-derived organoids - Alsaadi, A; Artibani, M; Hu, Z; Wietek, N; Morotti, M; Santana Gonzalez, L; Soleymani Majd, H; Ahmed, A (Cell Press, 2023)
The study of fallopian tube (FT) function in health and disease has been hampered by limited knowledge of FT stem cells and lack of in vitro models of stem cell renewal and differentiation. Using optimized organoid culture conditions to address these limitations, we find that FT stem cell renewal is highly dependent on WNT/β-catenin signaling and engineer endogenous WNT/β-catenin signaling reporter organoids to biomark, isolate, and characterize these cells. Using functional approaches, as well as bulk and single-cell transcriptomics analyses, we show that an endogenous hormonally regulated WNT7A-FZD5 signaling axis is critical for stem cell renewal and that WNT/β-catenin pathway-activated cells form a distinct transcriptomic cluster of FT cells enriched in extracellular matrix (ECM) remodeling and integrin signaling pathways. Overall, we provide a deep characterization of FT stem cells and their molecular requirements for self-renewal, paving the way for mechanistic work investigating the role of stem cells in FT health and disease.